Effects of depomedroxyprogesterone acetate on the development and maintenance of Candida albicans in the vagina of oophorectomized Wistar rats (Rattus norvegicus) - Agenor Storti-Filho; Edilson Damke; Márcia Aparecida Carrara; Marcia Regina Batista; Lucélia Donatti; Cinthia Gandolfi Boer; Terezinha Inez Estivalet Svizdinski; Márcia Edilaine Lopes Consolaro (Universidade de São Paulo, 2011)
The objective of this study was to determine the effect of medroxyprogesterone acetate (DMPA) on the development and maintenance of Candida albicans in the vagina of oophorectomized Wistar rats. The animals were divided into negative control groups (NCG), which received injections of sterile saline; positive control groups (PCG), which were given injections of estradiol valerate; and progesterone groups (PG), which were given injections of Depo-Provera®. After one week of hormonal induction, vaginal infection by C. albicans was induced in all the groups and detected by vaginal yeast culture and Papanicolaou smear. In addition, scanning and transmission electron microscopy images were obtained to confirm the vaginal infection by yeast in PG. A difference in progesterone levels in PG was observed between the basal level and after hormonal induction (P<0.0001). In this group, 100% of the rats acquired vaginal infection in the first week, but did not maintain it until the third week. The pharmaceutical brand of DMPA was effective for inducing the metestrus or diestrus phase of the estrous cycle in rats, similar to the use of pure progesterone. In contrast to estrogen treatment, progesterone alone could not support an experimental vaginal infection by C. albicans for any significant period of time. O objetivo do presente estudo foi determinar os efeitos do acetato de depomedroxyprogesterona (ADMP) no desenvolvimento e manutenção de Candida albicans na vagina de ratas Wistar ooferectomizadas. Os animais foram divididos em grupos controle negativos (GCN), que receberam injeções de salina estéril; grupos controle positivos (GCP), que receberam injeções de valerato de estradiol; e grupos progesterona (GP), nos quais foram feitas injeções de Depo-Provera®. Após uma semana da aplicação hormonal, foi induzida a infecção vaginal por C. albicans em todos os grupos, detectada por cultura para leveduras vaginais e esfregaço de Papanicolaou. Foram feitas ainda imagens por microscopia eletrônica de varredura e transmissão para confirmar a infecção pela levedura no GP. Foram observados diferentes níveis de progesterona em GP, entre os valores basais e após a indução hormonal (P<0,0001). Neste grupo, 100,0% das ratas contraíram a infecção vaginal na primeira semana, mas não a mantiveram até a terceira semana. A forma farmacêutica de ADMP foi efetiva em induzir as fases de metaestro e diestro do ciclo estral das ratas, da mesma forma que usando progesterona pura. Em contraste com o que ocorre no tratamento com estrógeno, a progesterona não pôde manter a infecção vaginal experimental por C. albicans por um período significativo de tempo.